Business analytics using R : a practical approach - Hodeghatta, Umesh R.; Nayak, Umesh (Apress, 2017)
Through examples and case studies, this thorough book explains practical business analytics through examples, covers the steps involved in using it correctly, and shows you the context in which a particular technique does not make sense. --